TRANSFORMATION OF THE THEATRICALIZATION OF POLITICAL LIFE IN THE CONTEXT OF CURRENT POLITICAL PROCESSES - BABAJANYAN, LEVON (Bulletin of Yerevan University E: Philosophy, Psychology, 2019)
Politics is a sphere of public activity, and as such contains some elements of theatricality and substitution. The formation of network society transforms the functional features of political theater. If at the first stage of the formation of the network society, the public participated in political game as a passive spectator, then through the formation of the network society, politics is theatricalized according to the principles of interactive theater. In the sociocultural environment of the network society, the uncertainty of the political plot, the elements of direct democracy, the rise of the level of influence of information technologies, the unpredictability and uncontrollability of political processes become important characteristics of the political game.
Keywords: political representation, theatricalization of politics, democracy of mood, shadowed and demagogic reality, network society, interactive politics